Irritable bowel syndrome: classification, dietary approach, pharmacological and psychological treatments - Ghamdi, Khalid Mohammed Al; Alghamdi, Mohammed Abdullah; Alqahtani, Huda Ali; Alsulami, Sari Ateeq; Alghamdi, Ali Mesfer; Aljohani, Abdullah Ahmed; Alqarni, Mohamed Awad; Al-Mulhim, Latifah Ibrahim; Bahadir, Nidhal Ibrahim; Aljdibi, Fahad Ibrahim; Ebrahim, Ahmed Mohamed (International Journal Of Community Medicine And Public Health, 2023)
Irritable bowel syndrome is a long-lasting disorder that affects a significant number of people worldwide. This comprehensive study explores the complexities of IBS, thoroughly investigating its classification, signs, and various treatment approaches. It emphasizes the nature of IBS symptoms, highlighting the importance of tailored treatment strategies that consider adjustments, medications, and psychological therapies. The study recognizes that each patient responds differently to treatments, underscoring the need for care. By shedding light on the nature of IBS and acknowledging experiences, this research aims to provide an updated and evidence-based understanding of managing IBS. The significance of an approach is emphasized, recognizing how health, psychological well-being, and lifestyle factors are interconnected in IBS. Alongside medication for symptom relief and therapies addressing aspects, dietary modifications play a vital role in improving patient outcomes and overall quality of life. This integrated strategy aims to address IBS's impact on health and overall well-being. In summary, this study provides information for healthcare professionals and researchers to provide an understanding of the complexities of IBS and advocate for a personalized and evidence-based approach to its treatment.